ジンコウ ジシン データ ノ サイカイセキ ニヨル ミズホ コウゲン ノ カブ チカク ハンシャハ ノ ケンシュツ - 伊藤, 潔; イトウ, キヨシ; 金尾, 政紀; カナオ, マサキ; ITO, Kiyoshi; KANAO, Masaki (1995)
P(論文) 下部地殼からの反射はさまざまな造山帯, 特に顕生代の拡大テクトニクス場において報告されているが, 南極大陸においてはこれまで反射法による地殼深部探査は行われていない。本研究では, 第21次日本南極地域観測隊(JARE-21)で行われた屈折法探査データを再解析し, その結果みずほ高原において下部地殼からの反射波を検出した。リュツォ・ホルム湾内の海中発破(薬量3トン)により, みずほルート上の約300kmに及ぶ測線上27観測点で記録が得られたが, このデータに8-15Hzのバンドパス・フィルターをかけた後, 速度を6.3km/sとしてnormal-moveout補正を行うと, 往復走時で8-16秒の範囲に顕著な反射波がみられた。これは下部地殼からの広角反射に対応し, その深さは18-48kmであることがわかった。この反射層の深さ分布は, 過去の内陸トラバース旅行で得られた重力異常, 特にブーゲ異常と良く対応しており, リュツォ・ホルム岩体の進化を研究する上でも重要である。 A reflective lower crust' has been found in some regions of Phanerozoic orogens. In Antarctica it has not been surveyed and is an important target for explosion experiments. Seismic refraction data from the explosion experiments during the 21st Japanese Antarctic Research Expedition (JARE-21) in 1981 were re-analyzed to detect reflected waves from the lower crust. An explosion in Lutzow-Holm Bay with 3000kg of explosive gave well-recorded seismic waves at 27 stations along a 300km profile on the northern Mizuho Plateau, East Antarctica. A band-pass filtered record section with a normal-moveout velocity of 6.3km/s shows clear phases of large amplitudes in a range of 8-16s of two-way travel time; these phases can be considered as wide-angle reflected waves from the lower crust. The reflection depths correspond to about 18-48km. The depth patterns of reflective layers on the Mizuho Plateau can be related to the Bouguer gravity anomalies and are useful for studying the evolution of the Lutzow-Holm Complex. departmental bulletin paper